2020
DOI: 10.2147/idr.s247378
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Real-World Study Comparing Various Antimicrobial Regimens for Bloodstream Infections Caused by Carbapenem-Resistant Gram-Negative Bacilli in a Tertiary Hospital, Shanghai, China, from 2010 to 2017</p>

Abstract: Background We conducted a real-world analysis of the effectiveness of different antibiotic regimens for bloodstream infections (BSIs) caused by carbapenem-resistant gram-negative bacilli (CR-GNB) in a Chinese population. Methods A retrospective observational study was conducted between January 2010 and December 2017. Patients with BSIs caused by CR-GNB confirmed by in vitro susceptibility tests were enrolled, and patient medical record data on antimicrobial agents and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…The remainder included multiple species of Gram-negative bacilli [15, 17-20, 22, 24, 26, 27, 29, 30, 33, 39, 48, 50, 53, 54, 59, 60]. Among eight studies all the participants were admitted to ICU [22,23,46,48,51,52,59,62].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remainder included multiple species of Gram-negative bacilli [15, 17-20, 22, 24, 26, 27, 29, 30, 33, 39, 48, 50, 53, 54, 59, 60]. Among eight studies all the participants were admitted to ICU [22,23,46,48,51,52,59,62].…”
Section: Resultsmentioning
confidence: 99%
“…Several different antimicrobial classes were used in the included studies for treatment of Gram-negative bacteremia; however, the detail provided in each study regarding the speci c antimicrobial used varied greatly [64]. Mortality 50 studies reported all mortality, of which ten reported 14-day mortality[16, 19,22,34,42,47,50,58,63,64], eleven reported 28-day mortality [14, 22, 25, 33, 40, 46, 50-52, 56, 57], twenty reported 30-day mortality [13, 15, 18, 20, 26, 28, 31, 32, 36, 37, 39, 41-44, 49, 55, 59-61, 63, 64], one reported 90-day mortality [53], seven reported infection-related mortality [13,15,22,24,25,45,49], and ten reported inhospital mortality [13,19,23,27,30,35,45,47,48,64].…”
Section: Resultsmentioning
confidence: 99%
“…The international consensus guidelines for the optimal use of polymyxins recommend that patients intravenous PMB should receive a dose of 1.25–1.5 mg/kg (equivalent to 12,500–15,000 IU/kg) PMB every 12 h infused over 1 h [ 16 ]. In one study, clinicians found that combination therapy with at least two in vitro active agents was associated with higher efficacy in treating bloodstream infections caused by CR-GNB [ 6 , 19 ]. Carbapenem was the agent combined most commonly with PMB, followed by tigecycline, and cefoperazone–sulbactam [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nephrotoxicity was observed in 7 patients (7%).Conclusions: Our results provide positive clinical and safety outcomes for PMB in the treatment of CR-GNB. Timely and appropriate use of PMB may be particularly useful in treating patients with sepsis in CR-GNB infections.caused by CR-GNB [6,18].Currently, there is a lack of data available on the e cacy, 28-day mortality, and adverse events for PMB in the treatment of CR-GNB infections. Here, we report on a multicenter, real-world study of patients receiving intravenous PMB to investigate the clinical outcomes of antimicrobial therapy in patients infected with CR-GNB.…”
mentioning
confidence: 99%